Preparation, characterization, and bioavailability of a phosphorylated human‐like collagen calcium complex. (29th June 2015) - Zhu, Chenhui; Chen, Yanru; Deng, Jianjun; Xue, Wenjiao; Ma, Xiaoxuan; Hui, Junfeng; Fan, Daidi
<x xml:space="preserve">Abstract</x> The aim of this study was to determine whether a phosphorylated human‐like collagen calcium (PHLC–Ca) complex showed a higher bioavailability than other calcium supplements. To improve the calcium‐binding ability of human‐like collagen (HLC), modified HLC was prepared by introducing a reactive phosphate group using a dry‐heating method, followed by the formation of PHLC–Ca in MOPS buffer. PHLC–Ca was characterized using atomic absorption spectrophotometry, Fourier transform infrared (FTIR), fluorescence quenching, circular dichroism (CD), and ultraviolet–visible absorption (UV–vis) spectroscopy. The calcium uptake test showed that the bioavailability of PHLC–Ca was higher than that of CaCl2 and G‐Ca. Data from a mouse model of osteoporosis suggested that PHLC–Ca is superior for treating osteoporosis than CaCl2 or G‐Ca. These results indicate that PHLC–Ca is a desirable calcium supplement for use in daily life and clinical application. Copyright © 2015 John Wiley & Sons, Ltd.